Recalculation of the relationship between effective peak ground and peak ground accelerations for earthquakes recorded in Costa Rica between 1983 and 2019 - Hidalgo-Leiva, Diego A. (2020)
In the present study, a calculation of the relationship between the effective peak acceleration and the peak ground acceleration is made. The database of accelerographic records of the Earthquake Engineering Laboratory of the University of Costa Rica, with events recorded between 1983 and 2019 was used. Five specific cases are analyzed. Two criteria are used in the selection of the records: i) 2 levels of maximum horizontal acceleration (2cm/s2 and 100cm/s2) and ii) the technology of the equipment that recorded the movement (Analog, Digital or a combination). The results show that there is an influence on the average values ​​of the effective peak acceleration / peak ground acceleration ratio, as the equipment technology varies, however, there are no significant variations related to the acceleration limits used. It is recommended that a ratio value of 0,870 be used instead of the currently used value of 0,800.